2020
DOI: 10.1002/edn3.154
|View full text |Cite
|
Sign up to set email alerts
|

Metabarcoding as a tool to enhance marine surveillance of nonindigenous species in tropical harbors: A case study in Tahiti

Abstract: Globalization has increased connectivity between countries enhancing the spread of marine nonindigenous species (NIS). The establishment of marine NIS shows substantial negative effects on the structure and functioning of the natural ecosystems by competing for habitats and resources. Ports are often hubs for the spread of NIS via commercial and recreational vessels. Prevention, detection, and mitigation efforts are required to avoid and manage the establishment of NIS in new ecosystems. In this study, metabar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 124 publications
(161 reference statements)
1
12
0
Order By: Relevance
“…This suggests that neither marker is more susceptible to differences in laboratory processing protocols and associated data biases. The 18S rRNA marker is more conserved than the COI , which typically results in comparatively lower species resolution and underestimation of species richness (von Ammon et al, 2018; Leray & Knowlton, 2016; Pearman et al, 2021). This may explain our observation of slightly stronger clustering of 18S rRNA data points according to the sample origin and substantial improvement of classification of 18S rRNA data sets following the removal of low‐quality samples (i.e., those with only a small number of resulting sequence reads).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that neither marker is more susceptible to differences in laboratory processing protocols and associated data biases. The 18S rRNA marker is more conserved than the COI , which typically results in comparatively lower species resolution and underestimation of species richness (von Ammon et al, 2018; Leray & Knowlton, 2016; Pearman et al, 2021). This may explain our observation of slightly stronger clustering of 18S rRNA data points according to the sample origin and substantial improvement of classification of 18S rRNA data sets following the removal of low‐quality samples (i.e., those with only a small number of resulting sequence reads).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the broadest investigation of non-indigenous invertebrates in Mediterranean marinas was conducted by Ulman et al (2017) with both modified RAS and scrapes by hand-held rigid net. During the last few years, the metabarcoding approach has also started to be employed in NIS surveys with satisfying results (see also Borrell et al, 2017;Miralles et al, 2021;Pearman et al, 2021). Metabarcoding can be considered as an efficient tool to detect cryptic species or early life stages, but one of the main disadvantages is the incompleteness of genetic sequence reference libraries (Zaiko et al, 2018;Duarte et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although members of the family Bougainvilliidae are found worldwide (Vannucci and Rees, 1961), the genus has been described as colonizing artificial surfaces in coastal waters (mostly ports and marinas) from the South Pacific Ocean, particularly in Australia (Wyatt et al, 2005;Grey et al, 2018), and New-Zealand (Schuchert, 1998;Cairns et al, 2009). A recent metabarcoding study of biofouling from submerged surfaces (buoys, ropes, tires, and pontoon structures) in Tahiti revealed the highest relative abundance of Bougainvillia among detected NIS (Pearman et al, 2021). Comparison of the seasonal recruitment of fouling hydroids on settlement panels between cold and warm months in Brazil, Migotto et al (2001) revealed that Bougainvillia spp.…”
Section: Recruitment Patterns Of Non-indigenous Species On Bio-polymersmentioning
confidence: 99%